The Militarization of State as a Factor of Geopolitical Competition - A. V. Tolochko; I. A. Zaitseva (Проблемы постсоветского пространства, 2017)
This article analyses the conception of collision between Russia and the West. It presents the history of U.S.-Soviet relations in the context of globalization. The authors note that, despite the end of the Cold War after breakup of the Soviet Union, the militarization of politics has not taken back seat as a geopolitical factor and has directly affected the various aspects of national and international security. The subject matter change of the participants in this process should be noted as a special feature of the militarization of modern globalization. The role of transnational and nongovernmental organizations escalating the situation in many unstable parts of the world is increasing. The neutral states and international organizations which purpose is far from of militarism begin to be enlisted for military and political actions. In the article the processes of geopolitical competition and militarization are considered on the example of the Russia-West confrontation and the bilateral relations between the superpowers are analyzed in the historical perspective. The article presents the uprise of the Cold War as a natural phenomenon. The Cold War was a deliberate policy of the US administration aimed at establishing of US dominance in the postwar world. This strategy involved the confrontation with its geopolitical opponents and not partnership relations. The USA could reach its foreign-policy goals only through the Cold War. One of the main methods of battle was the arms race aimed at the economic attenuation of the USSR. The paper focuses on the problems in the relations between Russia and the USA at the contemporary stage. The article designates the role of Russia which is countering and responding the expansion of geopolitical competition as well as projecting of its national achievements and spiritual values in the world. The article considers in the context of geopolitics and the militarization of the country the reform of power structures conducted in the Russian Federation and the functions of the Federal Agency of the Russian Guard’s troops. The founding of this structure is caused in many respects by the geopolitical situation developed at the beginning of the XXI century and requiring the rethinking of the "national security" concept and the change of national security priorities. The analysis of challenges and threats to the security of the Russian Federation in today's global world shows that the military constituent plays a significant role in its security content. The article determines potential threats to Russia's national security which have geopolitical, geo-economic, military and resource specificity.